Pengaruh Variasi Kecepatan Putaran Spindle dan Kedalaman Pemakanan Terhadap Kekasaran Permukaan Alumunium ADC12 pada Mesin Bubut CNC Okuma L150T - Jamaludin Jamaludin (Fakultas Teknik - Universitas Bung Karno, 2023)
In the rapidly growing manufacturing industry, especially in the field of machining, the use of computer systems has become increasingly prevalent. Consumer demands for precise workpieces with consistent quality, quick completion, and large quantities can be more easily achieved using CNC (Computer Numerical Control) machine tools compared to conventional machine tools. To determine the influence of spindle rotational speed and feed depth variation on the surface roughness of ADC12 aluminum in the Okuma L150T CNC lathe, an experimental study was conducted. Aluminum ADC12 specimens were used, and variations in spindle rotational speed and feed depth were tested for surface roughness using a Mitutoyo SJ-210 surface roughness tester. The obtained data were then analyzed and discussed based on statistical correlation and hypothesis testing. From the results of this study, the following conclusions can be drawn: (1) There is an influence of spindle rotational speed variation. At speeds of 900 rpm, 1500 rpm, and 2100 rpm, the average surface roughness levels of the workpiece were 7.45 μm, 6.35 μm, and 5.23 μm, respectively. Therefore, higher spindle rotational speeds result in lower surface roughness of the workpiece. (2) There is an influence of feed depth variation. At depths of 0.25 mm, 0.50 mm, and 0.75 mm, the average surface roughness levels of the workpiece were 5.23 μm, 6.32 μm, and 7.42 μm, respectively. Thus, deeper feed depths lead to higher surface roughness of the workpiece. (3) The combination of feed depth variation and spindle rotational speed that resulted in the workpiece with the lowest average surface roughness was achieved at a feed depth of 0.25 mm and spindle rotational speed of 2100, which amounted to 5.23 μm.